Antihumanist modernism in biopolitical junkyards of controlled remediation and risk. Issue 9 (1st September 2020) - Jaffe, Aaron
ABSTRACT: This essay proposes a new reading of modernism as a mode for separating the signal from the noise in conceptions of the human after humanism. It expands on a theory of second modernism which I have outlined in previous works, and by which the scene of modernist value is one of perilous event horizon, dictated by systematic ambivalences in modernity that have conventionally been obscured in Modernist studies. The following work tracks a succession of such risky horizons – moving between analyses of a significant but largely unremembered radiological disaster at Goiânia, Brazil in the late 1980s, J.G. Ballard's 1960s story 'The Terminal Beach', Shumon Basar, Douglas Coupland, and Hans Ulrich Obrist Ballard-inspired piece The Age of Earthquakes, and the theories of Czech-Brazilian media theorist Vilém Flusser. Through these materials, modernity and modernism are identified as chimerical non-spaces – characterised by the accumulation of data without shape or purpose, of connectivity without content, and the expectation of redemptive catastrophe, consigned to the past prior even to the point of conception.